Website files: imagematch.bodleian.ox.ac.uk:8000 - Systems and Services, B (University of Oxford, 2020)
This is a closed internal dataset containing websites files relating to imagematch.bodleian.ox.ac.uk:8000. These files were archived as part of the LIB702 Web Application Rationalisation Project (2019-2020) ran by Bodleian Digital Library Systems and Services. Due to the size of the site the files could not be saved to the GitLab LegacySite project space (https://gitlab.bodleian.ox.ac.uk/legacysites). The ORA UUID relating to this record has instead been added to GitLab to enable retrieval if necessary. Website files for this record are held within a separate dataset. Please refer to 'Website files: ballads.bodleian.ox.ac.uk' (https://ora.ox.ac.uk/objects/uuid:4fd7040c-60e1-4f95-bbd4-900e2f1a9b98).